Differential phenolic production of Vitis vinifera cv. Alvarinho leaves affected with Esca disease - Lima, M. R. M. (2006)
Esca is a destructive disease that affects Vitis vinifera around the world leading to important losses in wine production. Information on the response of Vitis vinifera plants to this disease is still scarce. To study the defence mechanisms of Vitis plants to Esca, we analysed leaves from both infected and non-affected boughs of Vitis vinifera cv. Alvarinho, of the Vinho Verde region (North of Portugal). Phenolics were analysed by HPLC-DAD-MS and by multivariate statistical analysis.